1987
DOI: 10.1042/bj2470441
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate transport by thermogenic-tissue mitochondria

Abstract: 1. Mitochondria isolated from the thermogenic spadices of Arum maculatum and Sauromatum guttatum plants oxidized external NADH, succinate, citrate, malate, 2-oxoglutarate and pyruvate without the need to add exogenous cofactors. 2. Oxidation of substrates was virtually all via the alternative oxidase, the cytochrome pathway constituting only 10-20% of the total activity, depending on the stage of spadix development. 3. During later stages of spadix development, pyruvate oxidation was enhanced by the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…In this study we showed that MPC can also be inhibited by Zaprinast. Inhibition or knockdown of MPC prevents pyruvate-dependent acetyl-CoA formation and O 2 consumption (5,6,42) and decreases the lactate/pyruvate ratio (43). Our study shows that Zaprinast and UK5099 not only block pyruvate-dependent mitochondrial O 2 consumption and citrate synthesis in brain mitochondria but also cause increases in pyruvate and aspartate and decrease in glutamate in brain mitochondria and the retina.…”
Section: The Effect Of Zaprinast On Glutamate and Aspartate Occurs Inmentioning
confidence: 63%
“…In this study we showed that MPC can also be inhibited by Zaprinast. Inhibition or knockdown of MPC prevents pyruvate-dependent acetyl-CoA formation and O 2 consumption (5,6,42) and decreases the lactate/pyruvate ratio (43). Our study shows that Zaprinast and UK5099 not only block pyruvate-dependent mitochondrial O 2 consumption and citrate synthesis in brain mitochondria but also cause increases in pyruvate and aspartate and decrease in glutamate in brain mitochondria and the retina.…”
Section: The Effect Of Zaprinast On Glutamate and Aspartate Occurs Inmentioning
confidence: 63%
“…maculutum were prepared as described by Proudlove et al (1987) and purified on a 21% (v/v) self-generating Percoll gradient as previously described (Moore et al, 1993a).…”
Section: Lsolation Of Mitochondriamentioning
confidence: 99%
“…The (26). The proportion of lipophilic ion accumulated free to respond to the mitochondrial membrane potential was calculated from the ratio of observed Rb+ distribution to that of TPMP+.…”
mentioning
confidence: 99%